Changing liver utilization and discard rates in clinical transplantation in the ex-vivo machine preservation era - Azizieh, Yara; Westhaver, Lauren P.; Badrudin, David; Boudreau, Jeanette E.; Gala-Lopez, Boris L. (Frontiers in Medical Technology, 2023)
Liver transplantation is a well-established treatment for many with end-stage liver disease. Unfortunately, the increasing organ demand has surpassed the donor supply, and approximately 30% of patients die while waiting for a suitable liver. Clinicians are often forced to consider livers of inferior quality to increase organ donation rates, but ultimately, many of those organs end up being discarded. Extensive testing in experimental animals and humans has shown that ex-vivo machine preservation allows for a more objective characterization of the graft outside the body, with particular benefit for suboptimal organs. This review focuses on the history of the implementation of ex-vivo liver machine preservation and how its enactment may modify our current concept of organ acceptability. We provide a brief overview of the major drivers of organ discard (age, ischemia time, steatosis, etc.) and how this technology may ultimately revert such a trend. We also discuss future directions for this technology, including the identification of new markers of injury and repair and the opportunity for other ex-vivo regenerative therapies. Finally, we discuss the value of this technology, considering current and future donor characteristics in the North American population that may result in a significant organ discard.